(3R,8aS)-3-Ethylperhydropyrrolo[1,2-a]pyrazine-1,4-dione - Bortoluzzi, Adailton J. (International Union of Crystallography, 2010)
In the title compound, C(9)H(14)N(2)O(2), the pyrrolidine and piperazine rings adopt envelope and boat conformations, respectively. The chiral centers were assigned on the basis of the known stereogenic center of an enantiomerically pure starting material and the trans relationship between the H atoms attached to these centers. The crystal packing is stabilized by an intermolecular hydrogen bond between the N—H group and a carbonyl O atom of the diketopiperazine group, forming zigzag C(5) chains along [010].